ORIGINAL PAPERPermanent cardiac pacing in adult patients with congenital heart disease after cardiac surgery - Trojnarska, Olga; Bręborowicz, Piotr; Ochotny, Romuald; Cieśliński, Andrzej (Archives of Medical Science, 2005)
Introduction: Impulse formation and conduction disturbances demanding permanent pacing are present in some adult patients with congenital heart disease (CHD). Almost half of these patients had a cardiac surgery in the past. The aim of this study was to analyze causes and modes of permanent cardiac pacing in this population. Material and methods: Data of 32 adult patients (20 women) mean age 28.4 years after pacemaker implantation were selected from a database of Adult Congenital Herat Disease Outpatient Clinic of the 1st Cardiology Department in Poznan. The mean age at the cardiac surgery in this group was 13.3 years. Results: The first implantation in this group was done at 20.5 years of age. In 25 patients a complete or advanced heart block was a cause of pacemaker implantation, in 12 directly after the cardiac surgery. Sinus node dysfunction was a reason of pacing in other 7 patients. In half of the cases the epicardial system was applied initially. A multiple implantation was done in 17 (double); 7 (triple) and 2 (quadruple). Conclusions: The necessity of permanent pacing in adult patients with CHD may appear directly after the operation as well as in long term follow up. Many of these patients need multiple pacemaker implantations during their life span. The implantation technique in CHD patients often differs from standard procedures in general “pacemaker” population. This requires from the implantation team a broad knowledge of defect anatomy and cardiac surgery mode.